2004
DOI: 10.1111/j.1460-9568.2004.03227.x
|View full text |Cite
|
Sign up to set email alerts
|

PACAP inhibits delayed rectifier potassium current via a cAMP/PKA transduction pathway: evidence for the involvement of IK in the anti‐apoptotic action of PACAP

Abstract: Activation of potassium (K(+)) currents plays a critical role in the control of programmed cell death. Because pituitary adenylate cyclase-activating polypeptide (PACAP) has been shown to inhibit the apoptotic cascade in the cerebellar cortex during development, we have investigated the effect of PACAP on K(+) currents in cultured cerebellar granule cells using the patch-clamp technique in the whole-cell configuration. Two types of outward K(+) currents, a transient K(+) current (I(A)) and a delayed rectifier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 61 publications
2
44
0
Order By: Relevance
“…Concerning the mechanisms involved, it has been shown that ethanol and PACAP exert an opposite effect on the delayed outward rectifier potassium current which in turn modulate caspase-3 activity that finally contributes to the control of granule cell survival [15]. The antiapoptotic effect of PACAP after oxidative stress may also play a major role in the protection of the brain during several forms of neuronal insult due to a decrease of blood flow and/or oxidative damage [18].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the mechanisms involved, it has been shown that ethanol and PACAP exert an opposite effect on the delayed outward rectifier potassium current which in turn modulate caspase-3 activity that finally contributes to the control of granule cell survival [15]. The antiapoptotic effect of PACAP after oxidative stress may also play a major role in the protection of the brain during several forms of neuronal insult due to a decrease of blood flow and/or oxidative damage [18].…”
Section: Discussionmentioning
confidence: 99%
“…11). The inhibitory effect of PACAP on potassium channels also contributes to the control of cell death (Zerr and Feltz, 1994;Mei et al, 2004;Castel et al, 2006). It has been proposed that activation by PACAP of the phosphatidylinositol 3Ј-OH kinase (PI3-K) neuroprotective pathway may synergize with the PKA cascade to promote cell survival (Fig.…”
Section: Actions Of Pituitary Adenylate Cyclase-activating Polypeptidmentioning
confidence: 99%
“…41,42 In addition, it has been described that PACAP mediates its neuroprotective effect, in part, by inhibition of delayed rectifier K(+) current (I(K)) via cAMP/PKA transduction pathway. 43,44 Moreover, the survival effect of PACAP could be mediated by others pathways. It has been demonstrated that PACAP promotes the increase of intracellular calcium from intracellular stores and calcium influx through calcium channels.…”
Section: Molecular Pathways Related To the Neuroprotection Of Cgnsmentioning
confidence: 99%